2017
DOI: 10.1093/ofid/ofx115
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mcr-1-Carrying Escherichia coli Causing Bloodstream Infection in a New York City Hospital: Avian Origins, Human Concerns?

Abstract: The spread of mcr-1 in the United States remains poorly defined. mcr-1-producing Escherichia coli that also carried blaSHV-12 was detected in a hospitalized patient. No additional cases were identified during screening of 801 Gram-negative isolates. Genomic sequencing identified an IncX4 mcr-1- harboring plasmid and ST117 clonal background associated with avian pathogenic E coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…To our surprise, three different variants of ESBL (namely, bla TEM-1B , bla TEM-99 and bla CTX-M-14 ) are present together with a newly-identified mcr-1 colistin resistance determinant in a single avian E. coli. Prior to this study, ST117 E. coli was only reported to contain mcr-1 in gut flora of children, China [30], and involved in bloodstream infections, in New York [32]. To the best our knowledge, our finding might define, for the first time, cooccurrence of integron-carrying ESBL (bla TEM-1B , bla TEM-99 and bla -CTX-M-14 ) and plasmid-bearing mcr-1 in a single ST117 E. coli isolate with avian origin from China, from 2011 to 2012.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our surprise, three different variants of ESBL (namely, bla TEM-1B , bla TEM-99 and bla CTX-M-14 ) are present together with a newly-identified mcr-1 colistin resistance determinant in a single avian E. coli. Prior to this study, ST117 E. coli was only reported to contain mcr-1 in gut flora of children, China [30], and involved in bloodstream infections, in New York [32]. To the best our knowledge, our finding might define, for the first time, cooccurrence of integron-carrying ESBL (bla TEM-1B , bla TEM-99 and bla -CTX-M-14 ) and plasmid-bearing mcr-1 in a single ST117 E. coli isolate with avian origin from China, from 2011 to 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, extended-spectrum b-lactamase (ESBL) also can be coproduced with MCR-1 in a single bacterial cell [26][27][28][29], indicating the complexity in the profile of MCR-1-participating antibiotic resistance. As for ST117 of E. coli [30], it is an endemic clone with avian origins [31], but human concerns [32]. In fact, the mcr-1-carrying ST117 has been recorded in inpatients with bloodstream infections [32] and predominantly inhabits in gut flora of children [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, after 25 days of colistin treatment, colistin resistant A. baumannii was isolated from intra-abdominal fluid of the patient. Colistin exposure is found to be the main risk factor for development of colistin resistance by previous studies (2, 8). We mimicked the effects of colistin exposure in the laboratory by measuring MIC and expressions of pmrCAB .…”
mentioning
confidence: 76%
“…The increase of colistin-resistance in Acinetobacter baumannii is a great concern in various regions of the world such as Asia, Europe, and North and South America (1). Exposure to colistin is considered as the most significant factor for emerging of colistin resistance (2), however, details of the in vivo response of A. baumannii to colistin exposure, such as the number of days for development of resistance was not described. The molecular studies about colistin resistance indicated two main mechanisms: modifications in lipid A structure and complete loss of LPS (3).…”
mentioning
confidence: 99%